2016
DOI: 10.1016/j.carbpol.2015.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity, cytotoxicity, genotoxicity and antigenotoxic effects of a cellulosic exopolysaccharide obtained from sugarcane molasses

Abstract: The acute toxicity, cytotoxicity, genotoxicity and antigenotoxic effects of BC were studied. Cytotoxicity of BC was evaluated in cultured C3A hepatoma cells (HepG2/C3A) using a lactate dehydrogenase (LDH) activity assay. Acute toxicity was tested in adults Wistar rats treated with a single dose of BC. The genotoxicity of BC was evaluated in vivo by the micronucleus assay. BC (0.33-170 μg/mL) added to C3A cell culture medium caused no elevation in LDH release over the background level recorded in untreated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 15 publications
2
35
0
3
Order By: Relevance
“…BC is a biomaterial, obtained by bacterial synthesis from sugarcane molasses (13), described in previous studies as a safe dressing with low toxicity (14), biocompatible (15), promoting growth and cell differentiation (17) and, thus, contributing to the healing process (9, 16, 17) and epithelialization (18). Preclinical and clinical studies have shown that this biomaterial is effective as a mechanical barrier and adjuvant in the treatment of surgical wounds (9) and in ulcerative injuries (17).…”
Section: Discussionmentioning
confidence: 99%
“…BC is a biomaterial, obtained by bacterial synthesis from sugarcane molasses (13), described in previous studies as a safe dressing with low toxicity (14), biocompatible (15), promoting growth and cell differentiation (17) and, thus, contributing to the healing process (9, 16, 17) and epithelialization (18). Preclinical and clinical studies have shown that this biomaterial is effective as a mechanical barrier and adjuvant in the treatment of surgical wounds (9) and in ulcerative injuries (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, Including experimental analyzes and clinical trials have shown that BC is non-toxic, biocompatible and effective for tissue remodeling [11][12][13][14] .…”
Section: Hronic Venous Disease (Cvd) Of the Lower Limbs (Ll) Ismentioning
confidence: 99%
“…In the present study, we used a cellulosic matrix, that has already been evaluated in biomechanical testing and biocompatibility as well as in cytotoxicity assays as a urethral reinforcing wrap in rats by evaluating its integration and remodeling to the host tissue (13, 18, 19). One of the main questions that we consider of interest in this evaluation is the change in the urethral wall layers thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, bacterial cellulose (BC), a biomaterial, has demonstrated efficacy as a driver cell and inductor in healing process (11, 12). Studies have proven its safety and efficacy in experimental and clinical models (11-13). …”
Section: Introductionmentioning
confidence: 99%